2020
DOI: 10.1620/tjem.251.313
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of MicroRNAs and Extracellular Vesicles in the Pathogeneses of Idiopathic Pulmonary Fibrosis and Acute Respiratory Distress Syndrome

Abstract: The lungs are the organs that work for gas exchange. The basic structure of the lungs is an alveolus, which consists of various types of parenchymal cells and bone marrow-derived cells. Therefore, because the lungs consist of various types of cells with various functions, communication among the different types of the cells should play important roles for the homeostasis and response to disease pathogens. In the past decades, researchers have focused on cytokines or adhesion molecules to reveal the intercellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 111 publications
(125 reference statements)
0
7
0
Order By: Relevance
“…Nonetheless, BALF proteomics applied to the study of interstitial lung diseases has gaining momentum and is providing reliable new results. In particular, growing efforts to investigate the role of extracellular vesicles in the physiopathology of interstitial lung diseases and their possible therapeutic applications have become more common in the scientific community [27,28], especially applied to idiopathic pulmonary fibrosis [13,14,17]. The few recent studies on EVs in BALF from IPF patients have mainly focused on nucleic acid content, such as miRNAs [16], whereas proteomic studies could provide valuable insights into the disease [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, BALF proteomics applied to the study of interstitial lung diseases has gaining momentum and is providing reliable new results. In particular, growing efforts to investigate the role of extracellular vesicles in the physiopathology of interstitial lung diseases and their possible therapeutic applications have become more common in the scientific community [27,28], especially applied to idiopathic pulmonary fibrosis [13,14,17]. The few recent studies on EVs in BALF from IPF patients have mainly focused on nucleic acid content, such as miRNAs [16], whereas proteomic studies could provide valuable insights into the disease [17].…”
Section: Discussionmentioning
confidence: 99%
“…In detail, Njock et al investigated exosomes from sputum of IPF patients, demonstrating a correlation of three specific exosomal miRNAs (miR-142-3p, miR-33a-5p, let-7d-5p) with disease severity [13]. Other reports have focused on serum EVs evaluation in IPF patients; for instance, Yamada et al proved a correlation of serum EV miR-21-5p with progression and prognosis of the disease [14]. Nonetheless, very few studies have investigated extracellular vesicles in BALF from IPF subjects and, most highlighted miR-NAs in EVs: for instance, Lee et al found miRNA-rich EVs in BALF from a healthy mouse model and set up a specific isolation protocol [15], while Liu et al investigated the expression pattern of miRNAs in exosomes from BALF of elderly IPF patients, identifying downregulation of miR-30a-5p in IPF subjects [16].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence demonstrated that under the influence of environmental factors and aging, epigenetic changes play an important role in IPF ( Kadel et al, 2019 ; Yamada, 2020 ; Yang and Schwartz, 2015 ). Epigenetic modifications include DNA methylation, histone modifications, and changes in the expression of non-coding RNA (especially microRNA) ( Chen et al, 2017 ).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Nonetheless, BALF proteomics applied to the study of ILDs could provide reliable new results. In particular, growing efforts to investigate the role of EVs in the physiopathology of ILDs and their possible therapeutic applications have become more common in the scientific community [27,28], especially applied to IPF [13,14,17]. The few recent studies on EVs in BALF from IPF patients have mainly focused on nucleic acid content, such as miRNAs [16].…”
Section: Discussionmentioning
confidence: 99%
“…In detail, Njock et al investigated exosomes from the sputum of IPF patients, demonstrating a correlation of three specific exosomal miRNAs (miR-142-3p, miR-33a-5p, let-7d-5p) with disease severity [13]. Other reports have focused on serum EVs evaluation in IPF patients; for instance, Yamada et al proved a correlation of serum EV miR-21-5p with progression and prognosis of the disease [14]. Nonetheless, very few studies have investigated EVs in BALF from IPF subjects and, most highlighted miRNAs in EVs: for instance, Lee et al found miRNA-rich EVs in BALF from a healthy mouse model and set up a specific isolation protocol [15], while Liu et al investigated the expression pattern of miRNAs in exosomes from BALF of elderly IPF patients, identifying downregulation of miR-30a-5p in IPF subjects [16].…”
Section: Introductionmentioning
confidence: 99%